Cahiers de prison : cahiers 14, 15, 16, 17, 18 - Gramsci, Antonio; Paris, Robert; Bouillot, Françoise; Granel, Gérard ([Paris] : Gallimard, 1990)
Bibliotheek François Vercammen
Frans
Meerdelige publicatie